Auditory selective attention in typical development and Auditory Processing Disorder - Stewart, Hannah J. (2017)
This thesis examines auditory selective attention as a possible cause of Auditory Processing Disorder (APD). APD is a diagnosis based on the clinical needs of the 5% of children who present with listening difficulties but demonstrate normal hearing. This thesis will focus on developmental APD, which affects children with no known infection, trauma or primary cause inducing their listening difficulties. It will seek to address the current lack of understanding of the root causes of APD, which leads to significant variation in clinical referral routes, resulting in inconsistent methods of diagnosis and treatment. APD has historically been approached via a bottom-up route of assessing auditory processing skills, such as temporal-spatial abilities. The inconsistent results of bottom-up studies has led to debate regarding the diagnosis and treatment of APD, resulting in extensive batteries of tests being conducted on children. However, recent evidence suggests that studies on the causality of APD should be refocused on top-down processes such as auditory attention and memory – hence the focus of this thesis on auditory selective attention. The thesis begins by assessing a new test of auditory selective attention, the Test of Attention in Listening (TAiL), to ensure that it measures auditory rather than supramodal attention. Having established the modality-specificity of TAiL, the thesis examines the development of auditory selective attention to both spatial and non-spatial auditory stimulus features, across tasks of varying levels of perceptual demand. Finally, the thesis assesses the selective attention ability of children with listening difficulties. Specifically, listeners’ selective attention is assessed in both the auditory and visual domains, using both spatially- and non-spatially-based tasks. If auditory selective attention deficits are found in those with listening difficulties, this will provide a basis for the diagnosis and treatment of APD to be constructed and managed from a psychological viewpoint rather than an audiological one.